B squared equals c squared minus a squared then to find B take the square root of you answer for b squared
n2 - 100 = (n + 10)(n - 10)
3c(squared)-17c-6 = 0 (3c+1)(c-6) = 0 c= negative one third or positive 6
It is: (c-4)(c-8) when factored
It is: (B -10)(B +10) when factored
They are 100 minus 49 = 51
100 minus 4 = 96
n squared minus n
2x squared minus 4
3x squared minus 25x minus 28
If your Problem is organized like this: A x squared plus B x plus C, the equation is: (B plus or minus the square root of(B squared minus 4 A C)) over 2A
How about: (3 squared minus 2 cubed) + 1 to the fourth 3 cubed minus 5 squared log 100 Kim Basinger's weeks minus Doris Day's cents.
No, unless "a" happens to be equal to 0, or to 1.
-22 - -22
x = ? 42 = x squared minus x
The formula for finding the angles is called " Pythagorean Thyrum " It states that a squred plus b squared equals c squared so therefore c squared minus a squared will equal b squared. i hope that helps
(a + b)2 - 100 = (a + b + 10)(a + b - 10).
b^3 - 25b^2 - 4b + 100 = 0 b = 25 or b = -2
there has to be more to the question is there a way you can tell what the equation equals
2x squared minus 5x minus 3 factored is (2x+1)(x-3).
the square root of b squared minus 4 times a times c